Learning from traditional built environment of Cyprus: Re-interpretation of the contextual values - Dinçyürek, Özgür; Türker, Özlem O. (Elsevier Ltd, 2007)
Last century witnessed the tragic results of ethnic separations between Turkish and Greek Cypriots, which were the two main communities of Cyprus Island. Both communities; that used to live mixed together on the same geography, shared the same history, culture, lifestyle and moreover the future. Nowadays, the bi-communal efforts on the Island, encouraged by the international society, provide the opportunity to union and heal the traces of the traumatic division. The new century promises a rapid increase in the welfare of Cypriots parallel to the solution of the political dispute. The sudden change in economical structure can increase the threat on the unique traditional environment as a result of unplanned and inevitable developments for fulfilling the rising demands. For the sake of having a contemporary living milieu, the traditional environment as the common architectural heritage of the Island can be revitalized, besides developing new appropriate architectural solutions in the light of the natural and cultural context. The Island's housing tradition bears the opportunity to be learned from the tried and evolved architectural solutions. Evaluating these values parallel to today's discourse, sustainable identity can be achieved by emphasizing especially the locality. In brief, this study tries to define the appropriate design principles for the contemporary housing developments and finds the ways of sustaining existing unique traditional patterns.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Cyprus, Migrations; Building traditions, Housing, Sustainability; Architectural heritage, ENGINEERING, ENVIRONMENTAL; housing, building traditions, architectural heritage; ENGINEERING, CIVIL, CONSTRUCTION & BUILDING TECHNOLOGY